Adult education & human resource development: Overlapping and disparate fields1. Issue 1 (January 2014) - Watkins, Karen E.; Marsick, Victoria J.
Abstract Adult education and human resource development as fields of practice and study share some roots in common but have grown in different directions in their histories. Adult education's roots focused initially on citizenship for a democratic society, whereas human resource development's roots are in performance at work. While they have grown in different directions, they also clearly overlap in important ways; through their focus on helping adults learn, a growing interest in constructivism in the knowledge era, and in broader international and national visions of the field. Differences are also noted, particularly in regard to emphasis on individual growth vs. growth of the organization. The article concludes with a look at three ways of looking at the relationship between the two fields: through the lens of practice, the metaphor of the big tent, and questions associated with philosophical differences.